Cultura y Corazón : A Decolonial Methodology for Community Engaged Research - Manzo, Rosa D., 1986-; Rivera-Lopez, Hector, 1949-; Flores, Yvette Gisele; Brazil-Cruz, Lisceth, 1982- (Book collections on Project MUSE., 2020)
"Cultura y Corazón is a cultural practice to research that requires a long term compromiso/commitment to community-based and engaged research methodologies. This book presents case studies in the fields of education and health that recognize and integrates communities' values, culture, and funds of knowledge in the research process"--